Proof: Do Control Map At Unchanged 1
Let's prove the following theorem:
if the following are true:
- expression state at time 1 = "begin_expr"
- Control Map at time 1 = [ ]
then Control Map at time 2 = [ ]
Proof:
Given
1 | expression state at time 1 = "begin_expr" |
---|---|
2 | Control Map at time 1 = [ ] |
# | Claim | Reason |
---|---|---|
1 | Control Map at time (1 + 1) = Control Map at time 1 | if expression state at time 1 = "begin_expr", then Control Map at time (1 + 1) = Control Map at time 1 |
2 | Control Map at time (1 + 1) = [ ] | if Control Map at time (1 + 1) = Control Map at time 1 and Control Map at time 1 = [ ], then Control Map at time (1 + 1) = [ ] |
3 | 1 + 1 = 2 | 1 + 1 = 2 |
4 | Control Map at time (1 + 1) = Control Map at time 2 | if 1 + 1 = 2, then Control Map at time (1 + 1) = Control Map at time 2 |
5 | Control Map at time 2 = [ ] | if Control Map at time (1 + 1) = Control Map at time 2 and Control Map at time (1 + 1) = [ ], then Control Map at time 2 = [ ] |
Comments
Please log in to add comments